Bamboonomic: Ekonomi Bambu Pendukung Desa Wisata Tegaren - Dwiridhotjahjono, Jojok; Wibowo, Prihandono; Nuryananda, Praja Firdaus (Jurnal Master Pariwisata (JUMPA); Volume 06, Nomor 02, Januari 2020, 2020)
Tegaren village is the biggest besek producer in Trenggalek, East Java. In collaboration with UPN "Veteran" of East Java, the people of Tegaren then developed an educational tourism that made besek as the main tourist attraction. Using the asset based community development (ABCD) method, leadership, and tourist gaze 3.0, the research team sought to make a scientific contribution to the development of the Tegaren’s tourism. After proceeding for one year, Tegaren’s people, especially women who made besek, began to feel the impact of improving the quality of life by the existence of a tourism village. There are three scientific arguments why besek, or bamboo, is used as the backbone of the development of the Tegaren’s tourism and later we call it as bamboonomic, namely 1) bamboo and besek have long been one of the heart of Tegaren’s life, 2) the tourism which was built based on natural assets and cultural assets creates ways of feeling as conceived in tourist gaze 3.0, and 3) this tourism is able to bring up and come up with leadership that brings Tegaren more advanced and prosperous. Keywords: besek, asset based community development, tourism, village, bamboo